THE SOLUTIONS TO THE PROBLEM OF SUICIDE THAISOCIETY ACCORDING TO THE THERAVADA BUDDHIST PHILOSOPHY - Santajitto (Phothised), PhraWitool; Bhavanabodhikun, Phrakhru; Leeka, Jaras (Journal of Graduate MCU KhonKaen Campus, 2020)
The aims of this research were: 1) to study committing suicide in the Buddhist philosophy; 2) to study the problem of committing suicide in Thai society; 3) to propose the solution ways to committing suicide in the Thai society according to the Theravada Buddhist philosophy. This study was carried out by means of a qualitative research methodology to collect the data by employing in-depth interviews of 30 key informants. The gathered data were presented by using a descriptive analysis method. The research results were as follows: 1) Buddhist philosophy does not agree with suicide as suicidal minds consist of greed, anger and delusion leading to take birth in the unwholesome realms. Buddhist philosophy also views that life is valuable, which can be developed to reach its ultimate goal, Nirvana. 2) Thailand has an average suicide statistics of 6.35 per hundred thousand people. In 2018, Khon Kaen province has an average of suicide 7.22 per hundred thousand people. Decisions of suicide committing are caused by 1) social problems 2) economic problems and 3) psychological problems. 3) The ways to solve the problem of suicide by using the following Buddhist philosophy are: 1) Four Ariyasacca Dhammas (Four Noble Truths) namely 1) knowing the problem, 2) finding reasons, 3) setting the goal, and 4) determining the method of solving; this is able to specify practical methods to achieve the goal of correctly solving the problems; 2) Tisikkhā (Threefold Training) used in Aṭṭhaṅgika-magga (Eightfold Noble Paths) used to solve social problems by Paññā Sikkhā (Training in Wisdom), economic problems by Sīla Sikkhā (Training in Precepts) and mental problems by Samādhi Sikkhā (Training in Mindfulness); 3) Sati (Consciousness) used to train the mind to stay at the present, regardless of the past and future with the power of Taṇhā (Craving).